Optical discs piracy: enforcement of the optical discs act 2000 in Malaysia / Ain-Maryam Zolkipli @ Zulkifli, Azzah Zatil Shadiqien and Fatin Mohammad Ismail - Zolkipli @ Zulkifli, Ain-Maryam; Shadiqien, Azzah Zatil; Mohammad Ismail, Fatin (Faculty of Law, 2012)
This is research was carried out for the purpose of finding to what extent the Optical Discs Act 2000 is being enforced, particularly on governing optical discs piracy in Malaysia. Through our interviews with a copyright owner, the Police and the Ministry of Domestic Trade, Cooperative and Consumerism in addition with our findings from books, reports, newspapers, journals and websites, we discovered the advantages of this Act and its loop holes. At the end of our findings, we note that the Act needs to be enforced strictly as the Act concerns the root of optical discs piracy which is the production of optical discs.